Caracterización fisicoquímica y cromatográfica del aceite esencial de hojas de Lantana camara L. - Vásquez Coral, Marines (2021)
The objective of the study was to characterize the essential oil of the leaves of Lantana camara L. (Verbenaceae), the extraction of the oil was carried out by hydrodistilation in a Karlsruhe equipment, the characterization by determining its physicochemical parameters and the identification of its components by analysis. high-performance gas chromatography system coupled to a mass spectrometry detector. The results were as follows: density 0.8326 g / cm3, Refractive index 1.4382, the colorful reaction was positive for components of an alcoholic nature. The chromatogram reported 26 components, 14 aliphatic hydrocarbons, 7 cyclic hydrocarbons, an arenic hydrocarbon, 2 sesquiterpenes, a diterpene (alcoholic) and an unidentified one. The most important components in order of percentage abundance were: aliphatic hydrocarbons 3-methyl heptane 19.823%, octane 18.150%, 2-methyl heptane 17.635%. The cyclic hydrocarbons 1,3-dimethyl cyclohexane 6.177%, 1.1 dimethyl cyclohexane 2.95%, a p-xylene hydrocarbon 2.25%, 2 sesquiterpenes caryophyllene oxide 1.71% and caryophyllene 1.47% respectively, the alcoholic diterpene phytol 0.68%. According to the result, we can specify that, because it contains a greater amount of hydrocarbons, its greatest comparative advantage for use would be as a natural fuel and solvent in the paint, lacquer and varnish industry. In addition, it would serve as the basis for preparing phytopharmaceuticals for use in traditional medicine to treat respiratory conditions and as an antipyretic.